Phloroglucinol Compounds and Their Derivatives: Comparison of FTIR, NMR, and Bioactivity Characterization as Antibacterial, Antioxidant, and Anticancer Agents - Sevi Dwi Cahyani; Triana Kusumaningsih; Maulidan Firdaus; Wahyu Eko Prasetyo (ALCHEMY Jurnal Penelitian Kimia, 2026)
Research on phloroglucinol (PG) and its derivatives has been extensively pursued over the past three decades. PG compounds are found in many plants, such as in the genus Callopyillum, the genus Hypericum, Eucalyptus kino, and brown algae. PG compounds have a symmetrical compound structure and contain many electrons distributed across three active sites, making them very advantageous for electrophilic aromatic substitution. PG has biological activities, such as antibacterial, antioxidant, anticancer, antiviral, anti-inflammatory, and others. PG bioactivity can be increased by synthesizing PG derivatives using various synthetic methods. The addition of an active group to PG can affect its bioactivity, properties, and characteristics, as well as its polarity and lipophilicity. This study aims to collect data on (1) Comparison of Fourier transform infrared (FTIR) and nuclear magnetic resonance (NMR) characterization of various PG derivative compounds, (2) Comparison of PG bioactivity and its derivatives as antibacterial, antioxidant, and anticancer compounds. PG compounds and their derivatives have been shown to exhibit antibacterial effects against several bacteria, including Staphylococcus aureus, Escherichia coli, and MRSA. Furthermore, PG derivatives exhibit antioxidant properties, as evidenced by their low IC50 values, and have demonstrated anticancer activity against cancer cell lines such as A549, MCF-7, and HTC-116. The findings of this study have the potential to assist researchers in developing new drugs.